PENGARUH KUALITAS TENAGA MEDIS TERHADAP PELAYANAN KESEHATAN (Di Puskesmas Kecamatan Ratahan Kabupaten Minahasa Tenggara) - MALINGKAS, VERONICA; TULUSAN, FEMMY (Sam Ratulangi University, 2018)
The research is motivated by the problems that are recorded. In Ratahan Subdistrict HealtCenter, Minahasa Regebcy, namely in the Effect of the quality of medical personnel on health servicesachieved optimally. This is alleged to have links that affect healt services. In doing healt, medicalpersonnel should have high performance and heven the quality of medical personnel who are in healtservices. Therefore, there is a need to to influence the quality of good medical personnel so that healthservice can improve good service for paserv pubictients. The quality of medical personnel is the level ofexcellence that is expected to the public service and control over the level of excellence to meet thedemands. Quality of service depends service on the ability to provide service on the ability to provideservices to meet the expectations. Health at Ratahan District Health Center. Southeast Minahasa. In thisstudy the method used is a quantitative method. While the data analysis technique used is correlationanalysis and simple analysisi to show the extebt of the relationship between the two variables. Based onthe research conducted and continued by analyzing the data obtained, the resukt is that a strong opinionis between the influence of the quality of medical personnel of 0.970. this means testing hypotheses isaccepted. From the result of the study obtained a correlation determination coefficient of 0.941% for 94%while the rest is the study.Keywords : effect Of Quality Of Medical Personnel, Health Service